2010
DOI: 10.3400/avd.ctiia09001
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Aortic Dissection: Elastic Fiber Abnormalities and Aortic Medial Weakness

Abstract: A lthough aortic dissection was previously a disease with an extremely poor prognosis, recent advances in diagnostic imaging and therapeutic modalities may improve its prognosis.1, 2) However, much of its etiology and pathogenesis remains unknown. In addition, new pathological variants of aortic dissection, such as intramural hematoma (IMH) and penetrating atherosclerotic ulcer, and related diseases have been identified, raising a new problem. Against this background, this paper revisits the basic pathology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 29 publications
1
23
2
Order By: Relevance
“…Conventional histological studies show that Marfan aortic samples are characterized by fragmentation and disorganization of elastic fibres, accumulation of amorphous matrix components, fibrotic collagen production, and loss of cells 12, 13 . Moreover, the elastin content in human Marfan aorta is almost 50 per cent lower 12, 16 , and scanning electron microscopy demonstrates a significant loss of interlamellar fibres that link neighbouring laminae 17 . To study Marfan disease process, mice have been genetically engineered to replicate the clinical spectrum of the human disease.…”
Section: Introductionmentioning
confidence: 95%
“…Conventional histological studies show that Marfan aortic samples are characterized by fragmentation and disorganization of elastic fibres, accumulation of amorphous matrix components, fibrotic collagen production, and loss of cells 12, 13 . Moreover, the elastin content in human Marfan aorta is almost 50 per cent lower 12, 16 , and scanning electron microscopy demonstrates a significant loss of interlamellar fibres that link neighbouring laminae 17 . To study Marfan disease process, mice have been genetically engineered to replicate the clinical spectrum of the human disease.…”
Section: Introductionmentioning
confidence: 95%
“…We introduced GRF glue in 1995, and experienced a large number of late false aneurysms. 2,11) Currently, reinforcement with fibrin glue and Teflon felt is conducted, and long-term results are favorable. A study reported the usefulness of BioGlue, 12) but a glue that may have a tissue toxicity should be carefully used.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,[11][12][13][14][15] In addition, its etiology and pathogenesis are poorly understood. 26) In the present guideline, the conservative treatment standard is not declared as thrombosed AAD. However, the surgical treatment standard is insisted upon.…”
Section: Discussionmentioning
confidence: 99%